Conditioning out‐of‐date bank‐stored red blood cells using a cell‐saver auto‐transfusion device: effects on numbers of red cells and quality of suspension fluid1. (10th June 2014) - Read, M. S.; Coles, P.; Pomeroy, M.; Anderson, E.; Aziz, M. I.
Summary We investigated the utility of a cell‐saver device for processing out‐of‐date red blood cells, by washing twenty bags of red blood cells that had been stored for between 36 and 55 days. The volume of recovered cells, and the characteristics of the suspension fluid, were measured before and after treatment. The ratio of free haemoglobin to total haemoglobin was up to 0.02 before processing, and up to 0.011 afterwards, changing by between −0.013 and +0.003. This ratio met the current standard for free haemoglobin (less than 0.008 in more than 75% of samples), both before and after processing. Ninety‐three percent of red blood cells survived the process. Potassium ion concentration fell from above 15 mmol.l−1 in all cases, to a mean of 6.4 mmol.l−1 (p < 0.001). The pH rose to a mean value of 6.44 (p = 0.001). Lactate ion concentration fell to a mean value of 14 mmol.l−1 (p < 0.001). Sodium ion concentration rose from a mean value of 93 mmol.l−1 to a mean value of 140 mmol.l−1 (p < 0.001). A useful proportion of out‐of‐date red blood cells remained intact after conditioning using a cell‐saver, and the process lowered concentrations of potentially toxic solutes in the fluid in which they were suspended.